The Incidence and Risk Factors for Lower Limb Skin Graft Failure. (15th July 2014) - Reddy, Sumeet; El-Haddawi, Falah; Fancourt, Michael; Farrant, Glenn; Gilkison, William; Henderson, Nigel; Kyle, Stephen; Mosquera, Damien
Abstract : Lower limb skin grafts are thought to have higher failure rates than skin grafts in other sites of the body. Currently, there is a paucity of literature on specific factors associated with lower limb skin graft failure. We present a series of 70 lower limb skin grafts in 50 patients with outcomes at 6 weeks. One-third of lower limb skin grafts went on to fail with increased BMI, peripheral vascular disease, and immunosuppressant medication use identified as significant risk factors.